Walking down Skeletal Muscle Lane: From Inflammasome to Disease - Nicolas Dubuisson; Romain Versele; María A. Davis-López de Carrizosa; Camille M. Selvais; Sonia M. Brichard; Michel Abou-Samra (Cells, 2021)
Over the last decade, innate immune system receptors and sensors called inflammasomes have been identified to play key pathological roles in the development and progression of numerous diseases. Among them, the nucleotide-binding oligomerization domain (NOD-), leucine-rich repeat (LRR-) and pyrin domain-containing protein 3 (NLRP3) inflammasome is probably the best characterized. To date, NLRP3 has been extensively studied in the heart, where its effects and actions have been broadly documented in numerous cardiovascular diseases. However, little is still known about NLRP3 implications in muscle disorders affecting non-cardiac muscles. In this review, we summarize and present the current knowledge regarding the function of NLRP3 in diseased skeletal muscle, and discuss the potential therapeutic options targeting the NLRP3 inflammasome in muscle disorders.